Patofisiologi Bisa Ular dan Aplikasi Terapi Tumbuhan Obat Antiophidia (Antibisa) - Aditya K. Karim; Ervina Indrayani; Laila Hanum (Jurusan Biologi FMIPA Universitas Cenderawasih, 2014)
Venomous snakebite is an important cause of morbidity and mortality, and is one of the major health problems in many regions of the world. Medicinal Plant which are effectively inhibitor and neutralize the snake venom and it is considered as a valuable source of natural products for development of medicines against venomous snake bite. The biomedical value of these natural inhibitors can lead to the development of new therapeutics for an assortment of diseases as well as contributing to efficient antivenoms for the treatment of ophidic accidents.Key words: pathophysiology, snake bite, envenomation, medicinal plant, therapeutic.